(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Today’s sports associations need to develop their management approach and pays attention to the quality development of athletes to be in line with developmentof The National Development Plan. Therefore, the management of the association is necessary to have knowledge, understanding, curiosity and systematic development of the association in relation to management approaches aimed at developing athletes and having higher potential.The main objectives wereto study components of the management model of Trang Provincial Sport Association and to develop the management model of Trang Provincial Sports Association. The survey method was used and divided into three parts (i) In-depth interviews from 5 experts by purposive random sampling (ii) Delphi technique, the sample group in the research was obtained by a method of purposive random sampling of 18 people as follows: (1) Two representatives from the sports policy management group of Thailand (2) Five groups of the experts were consisted of one representative of the executive director at the policy level of the Tourism and Sport Department, three representatives those who were the executive committee from sport associations, two representatives those who were the secretary, or the sport club president, four representatives those who experts in administration, and six representatives those who were the stakeholders. (iii) Focus Group was obtained by purposive random sampling all total 9 people those who were examined for suitability and feasibility of implementation with three persons of the club’s executive committee, three persons of the club secretary, three persons of the sports professionals or athletic trainers. The investigators found that the management model of the Trang Provincial Sports Association, the study was able to synthesize the management components of the Trang Provincial Sports Association which can be divided into 9 areas: 1. Trainers 2. Sports Science 3. Sport facility 4. Budget 5. Organization Management 6. Training 7. Recruiting 8. Performance 9. Supporting.